Global Tomato Production: Price Sensitivity and Policy Impact in Mexico, Türkiye, and the United States - Ramu Govindasamy; Rahmiye Figen Ceylan; Burhan Özkan (Horticulturae)
Tomato, a vital subtropical vegetable crop, is in demand globally but is produced in limited regions. Recently, its supply has become increasingly influenced by internal and external production factors. This study analyzed the impact of price fluctuations and evolving agricultural support schemes on tomato production in three key producers: Mexico, Türkiye, and the United States, which play significant roles in the global market with specialized production and trade. Using time-series price response data from 1991 to 2022, the research examined market prices, government support policies, and international trade agreements. Long-term price effects were similar in Türkiye and the USA but negligible in Mexico. Short-term price differences were positive across all countries, with the strongest impact in the USA. Financial support programs increased supplies in alignment with time-based effects. Deviations from long-term equilibrium were corrected in all countries, with Türkiye showing the fastest recovery. The results suggest that decoupled supports positively influence supply and merit further promotion.